Unilateral variant brachial plexus - Sontakke, YA; Joshi, M; Marathe, RR (Journal of College of Medical Sciences-Nepal, 2012)
Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 49-54 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6681